Compatibility between variable taper mechanized instruments and corresponding gutta-percha cones: photomicrograph analysis - Feitosa, Márcia Eugênia de Sousa Damasceno; Rosa, Gabriela Martins Rodrigues; Luna-Cruz, Suyane Maria; Pinheiro-Júnior, Elilton Cavalcante; Vivacqua-Gomes, Nilton; Vasconcelos, Bruno Carvalho de (Brazilian Dental Science, 2024)
Objective: This study aimed to assess the compatibility between variable taper NiTi instruments and corresponding gutta-percha cones. Material and Methods: Protaper Gold F2 (F2/PTG), Wave One Gold Primary (PRI/WOG), and Reciproc Blue R25 (R25/RB) instruments (n = 3) were included, along with corresponding gutta-percha cones (n = 10), produced by the manufacturers and from three other brands (Diadent, MK Life, and Tanari). Images of both instruments and cones were obtained through photomicrographs using a digital microscope (500x). The instruments were photographed at seven angles, rotating on their axis to record the maximum diameter at desired levels; the gutta-percha cones, due to their cross-section, were photographed only once. The images were analyzed using Image J software by a blinded operator at 1.0 (D1), 6.0 (D6), and 12.0 (D12) millimeters from their tip. ANOVA and Tukey tests were employed for statistical analysis, with significance set at 5.0%. Results: Considering the correspondence between F2/PTG and PRI/WOG instruments, significant differences were observed when the manufacturer’s cones were analyzed (P < 0.05). In relation to R25/RB instruments, statistical differences were observed only for the Tanari cone at D1 (P < 0.05). Conclusion: Within the study’s limitations, it can be concluded that the tested instrument systems and dedicated gutta-percha cones exhibited some dimensional variability among them. Furthermore, among the evaluated cones, the cones corresponding to F2/PTG and PRI/WOG instruments from the manufacturer itself showed the greatest discrepancies.KEYWORDSEndodontics; Gutta-Percha; Photomicrography; Root canal preparation; Root canal obturation.